SHIFTING TO E-MOBILITY: CHALLENGES AND ACCOMPLISHMENTS IN CEE AUTOMOTIVE INDUSTRY - SARMIZA PENCEA (Global Economic Observer)
The European Union (EU) is currently undergoing considerable simultaneous challenges pertaining to climate change, in the context of its commitment to achieving climate neutrality by 2050. In pursuing the decarbonisation goal that underlies the assumed energy transition, a shift from fossil-fuelled to electric vehicles (EVs) represents a crucial step. In this context, the objective of our article is to conduct a comprehensive analysis of three key areas: (a) the potential impact of road transport electrification on the automotive industry in Central and Eastern European (CEE) countries and Romania; (b) the current state of development of battery cell production for EVs in each of these states; and (c) the prospects for implementing the transition to e-mobility in the region.